Correction: Multifunctionalized polyurethane–polyurea nanoparticles: hydrophobically driven self-stratification at the o/w interface modulates encapsulation stability. Issue 42 (30th September 2015) - Rocas, Pau; Fernández, Yolanda; Schwartz, Simó; Abasolo, Ibane; Rocas, Josep; Albericio, Fernando
Abstract : Correction for 'Multifunctionalized polyurethane–polyurea nanoparticles: hydrophobically driven self-stratification at the o/w interface modulates encapsulation stability' by Pau Rocas et al., J. Mater. Chem. B, 2015, DOI: ; Web:10.1039/c5tb01345c .